Advanced Therapy Medicinal Products for Rare Diseases: State of Play of Incentives Supporting Development in Europe - Farkas, Andreas M.; Mariz, Segundo; Stoyanova-Beninska, Violeta; Celis, Patrick; Vamvakas, Spiros; Larsson, Kristina; Sepodes, Bruno (Frontiers in Medicine, 2017)
In 2008, the European Union introduced the Advanced Medicines Regulation aiming to improve regulation of advanced therapy medicinal products (ATMPs). We applied the ATMPs classification definitions in this Regulation to understand the link of this emerging group of medicinal products and the use of the Orphan Regulation. A total of 185 products that can be classified as ATMPs based on this Regulation have been submitted for orphan designation. Prior to its introduction in 2008, 4.5% of the products submitted for orphan designation met these criteria. This percentage went up to 15% after 2008. We analyzed several parameters associated with active ATMP ODDs focusing on sponsor type and EU-Member State origin, therapeutic area targeted, and ATMP classification [i.e., somatic cell therapy medicinal product, tissue-engineered product (TEP), or gene therapy medicinal product (GTMP)] and the use of regulatory services linked to incentives such as the use of protocol assistance (PA) and other Committees [Committee for Advanced Therapies (CAT) and the Pediatric Committee]. The aim here was to gain insight on the use of different services. The UK submits the largest number of ATMPs for ODD representing 30% of the total to date. Few submissions have been received from central and Eastern European Member States as well as some of the larger Member States such as Germany (3.6%). ATMPs ODDs were primarily GTMPs (48.7%) and SCTMPs (43.3%). TEPs only represented 8% of all submissions for this medicinal class. This is different from non-ODDs ATMPs where GTMPs make only 20% of ATMPs. A total of 11.7% of ATMP ODDs had received formal CAT classification. A total of 29.8% of all orphan drug (OD) ATMPs requested PA. A total of 71.8% did not have an agreed pediatric investigation plan (PIP). Four products (Glybera one PA; Zalmoxis two; Holoclar one; Strimvelis three) have received a marketing authorization (MAA) and a 10-year market exclusivity. Strimvelis also completed their PIP, which was compliant and received the additional 2-year extension to their 10-year market exclusivity. One OD ATMP (Cerepro) received a negative opinion for MAA. The use of services linked to incentives offered by different legislations for ATMP ODDs is low, indicating a need for increasing awareness.